Human Short Peptidoglycan Recognition Protein PGLYRP1/Tag-7/PGRP-S Inhibits Listeria monocytogenes Intracellular Survival in Macrophages - Slonova, Darya; Posvyatenko, Alexandra; Kibardin, Alexey; Sysolyatina, Elena; Lyssuk, Elena; Ermolaeva, Svetlana; Obydennyi, Sergei; Gnuchev, Nikolay; Georgiev, Georgii; Severinov, Konstantin; Larin, Sergey (Frontiers in Cellular and Infection Microbiology, 2020)
PGLYRP1/Tag-7/PGRP-S is one of mammalian peptidoglycan recognition proteins (PGRPs). Here, we demonstrate that human recombinant PGLYRP1/Tag-7/PGRP-S potentiates the response of murine macrophage-like ANA-1 cells and human macrophages to facultative intracellular pathogen Listeria monocytogenes. PGLYRP1/Tag-7/PGRP-S binds to the surface of L. monocytogenes and other bacterial cells but has no effect on their growth in culture. While PGLYRP1/Tag-7/PGRP-S treatment modestly enhanced phagocytosis of bacteria by ANA-1 cells, the intracellular survival of PGLYRP1/Tag-7/PGRP-S treated L. monocytogenes was strongly inhibited 2 h after internalization. PGLYRP1/Tag-7/PGRP-S treatment of bacteria boosted oxidative burst induction and increased the level of proinflammatory cytokine IL-6 produced by ANA-1, however, these effects happened too late to be responsible for decreased intracellular survival of bacteria. Our results thus suggest that PGLYRP1/Tag-7/PGRP-S acts as a molecular sensor for detection of L. monocytogenes infection of mammalian cells that leads to increased killing through a mechanism(s) that remains to be defined.